Perlindungan Hukum Data Kesehatan Pasien di Era Digital: Legal Protection of Patient's Health Data in The Digital Era - Fauziah, Yessy Andriani; Susanto, Dany Agus; Utama, Yudhistira Prawira (Magister Ilmu Hukum - Universitas Hang Tuah, 2026)
Digital transformation in the health sector has accelerated cross platform data exchange, while at the same time increasing the risks of privacy violations and patient information leakage. Law Number 27 of 2022 on Personal Data Protection and Law Number 17 of 2023 on Health emphasize the importance of secure and accountable medical data governance in Indonesia. This article aims to analyze the adequacy of legal protection for patient health data, with particular attention to regulatory coherence and existing normative gaps in the implementation of these two laws, as well as their relationship with the principles of medical ethics. This study applies a normative legal research method using a statutory approach, a conceptual approach, and a comparative approach. The statutory approach examines relevant legislation governing health data protection, while the conceptual approach explores ethical principles such as patient autonomy, confidentiality, and accountability. The comparative approach draws lessons from international regulatory practices to provide broader context. The findings indicate that although patient health data protection is explicitly regulated, significant gaps remain in practice, particularly regarding security standards, system interoperability, and the quality of digital consent. These weaknesses may undermine patient trust and increase legal and ethical risks. Therefore, this study recommends the implementation of Data Protection Impact Assessments, independent audits, and the integration of digital ethics into health professional education to strengthen accountability and sustain public trust, following best practices adopted in the European Union and the United States